All American boys [book club bag] - Reynolds, Jason; Kiely, Brendan, 1977- (Atheneum Books for Young Readers, 2015)
When sixteen-year-old Rashad is mistakenly accused of stealing, classmate Quinn witnesses his brutal beating at the hands of a police officer who happens to be the older brother of his best friend. Told through Rashad and Quinn's alternating viewpoints.